Two-Dimensional Reconstructed Image of a Subsurface Structure Using Continuous Scanned Photothermal Imaging - Kim, Moojoong; Kim, Hyunjung (Photonic Sensors, 2025)
This study presents the two-dimensional (2D) image of a subsurface structure reconstructed using an imaging method based on the photothermal effect. The photothermal imaging method is based on the deflection method using two lasers: pump and probe lasers. A continuous scanning technique is proposed for 2D (x- and y-directions) surface scanning. The continuous scanning method is compared with the conventional point-by-point scanning technique, and a low-pass fast Fourier transform filter and a Marr-Hildreth detector are found to produce significant results. The photothermal imaging method with continuous 2D surface scanning is performed on three copper-resin double-layer samples with different subsurface structures. The subsurface structures of the copper-resin double-layer samples comprise a square block of 5×5 mm2 area and blocks shaped as the alphabet letters “T” and “F”. The letters are 3 mm wide and 10×13 mm2 in area. All three shapes are 1 mm thick and located at a depth of 0.5 mm from the surface of the copper block. The reconstructed photothermal images show an absolute error within 0.122 mm compared with the actual subsurface structure, equivalent to a 2.3% relative error.
Keywords: Continuous scanning; Imaging method; Nondestructive tests; Photothermal effects; Photothermal imaging; Reconstruction; Scanning techniques; Subsurface structures; Surface scanning; Two-dimensional; nondestructive test; Photothermal effect; photothermal imaging; reconstruction; tomography; visualization